Sex estimation using coronal measurements of permanent canines in a contemporary mestizo population from Manizales, Colombia - Yepes-López, Viviana Andrea; Luna, Leandro Henán; Gómez-Mejía, Juliana (Revista Facultad de Odontología Universidad de Antioquia, 2019)
Introduction: sex estimation is one of the most important aspects of bioanthropological analysis. Teeth are a key tool to obtain this information, especially in cases where the action of taphonomic agents or funeral characteristics are unfavorable for preservation. The aim of this study was to examine the degree of sexual dimorphism in permanent canines of a contemporary mestizo population from the city of Manizales, Colombia. Method: descriptive study, measuring the mesiodistal (MD) and bucolingual (BL) diameters of permanent canines in 109 mestizo individuals (63 male and 46 female) aged 15 to 18, born in the city of Manizales, Colombia. The used statistical methods helped obtain the cut-off points, the percentages of cases correctly allocated, the likelihood estimation for new individuals and the sexual dimorphism values. Results: the cut-off points were 7.88 mm and 7.33 mm for MD and BL of the upper canine, respectively, and 6.81 mm and 6.76 mm for the same variables in lower canines. Correct allocations range from 71.42% to 78.26%, except for bucolingual diameter in the upper canine, which yielded low values. The correct likelihood estimation of external individuals ranges from 0.71 to 0.83. Finally, sexual dimorphism is relatively low (between 2.79% and 6.80%), although it falls within the expected range. The most dimorphic tooth is the lower canine, in line with reports in other populations around the world. Conclusions: the size of permanent canines is a good predictor of sex in the studied population and can be used when other osteological indicators are not available, or as a complement to them